CORPORATE GOVERNANCE DISCLOSURE PRACTICES AND FIRM’S FINANCIAL PERFORMANCE - Parvathy M. D , Dr. P. Balasubramanian (International Journal of Advanced Science and Technology, 2020)
The present study investigates the relationship between corporate governance and the overall financial performance in the emerging Indian context. The relevance of corporate governance increased in the liberalized economic environment due to the integration of countries into the world market. Fast Moving Consumer Goods (FMCG) sector is India’s fourth largest industry, contributing almost 20 percent to Gross Domestic Product (GDP). The study is to evaluate the influence of corporate governance in the overall financial performance of the selected organizations in the FMCG sector. Corporate Governance Disclosure Index (CGDI), used for identifying the corporate governance compliance status and panel data technique is used to investigate the extent of influence by corporate governance on the financial performance.